A 2-year pure biochar addition enhances soil carbon sequestration and reduces aggregate stability in understory conditions - Jiabin Wei; Youqing Li; Juan Li; Wei Yan; Qi Yin; Hongwei Jiang; Zongling Li; Jinyu Jiang; Yu Li; Yu Yao; Lang Zhang (Scientific Reports)
Abstract The enhancement of soil aggregate size and stability is crucial for mitigating climate change and improving carbon sequestration in forest ecosystems. Biochar, derived from rice husks, has been suggested as an effective mean to increase soil carbon storage. However, isolating biochar’s specific effects on soil aggregate formation and carbon sink capacity can be complex due to the overlapping influences of fertilization and understory vegetation cultivation. Our study circumvented these variables by incorporating different amounts of biochar into plantation soil without any additional cultivation or fertilization, conducting a detailed two–year field experiment. The findings revealed that biochar significantly increased the organic carbon content and density in the uncultivated under–forest Ferralsols, thus enhancing its carbon sink function. Intriguingly, while biochar raised the proportion of small soil aggregates (< 0.25 mm) and their organic carbon levels, it decreased the fraction of larger aggregates (> 0.25 mm), adversely affecting soil aggregate stability. These results suggest that biochar may compromise soil aggregate structure and stability in the absence of plant growth. The positive impact of biochar on soil carbon storage was found to depend more on its inherent inert carbon content than on soil type. Moreover, biochar alone was insufficient to increase the quantity of soil macroaggregates without the binding action of plant root exudates. Biochar’s key function appears to be in enhancing the soil aggregate–forming processes facilitated by plant roots and microorganisms. Therefore, for optimal carbon sequestration in forest soils, integrating biochar application with appropriate agricultural practices is advisable.